Evaluation of nutritional, anti-nutritional and mineral content of amaranths species grown in Gamo and Konso zone, Southern Ethiopia - Eyesa, Wasihun Wale; Yadda, Tuma Ayele; Badebo, Ermais Dureto; Tessema, Melese Lema (International Journal of Agricultural Research, Innovation and Technology, 2023)
Amaranth (Amaranthus sp.) is an underutilized pseudo-cereal with excellent nutritional and functional properties. The nutritional compositions, anti-nutritional and mineral content of two Amaranth species were evaluated by using standard procedures. Completely Randomized Design (CRD) was used for nutritional, anti-nutritional and mineral content with two treatments and five replications. The nutritional compositions of Amaranthus cruentus and Amaranthus hypochondriacus were shown a significant difference (p<0.05) in mean scores excepting moisture content. Phytate and oxalate content of A. cruentus and A. hypochondriacus were shown a significant difference (p<0.05), but tannin content did not show a significant difference (p<0.05). The calcium, iron and zinc content of A. cruentus and A. hypochondriacus were shown a significant difference (p<0.05) in mean, scores. The Amaranth grain species were rich in crude protein, fat and fiber as compared to common cereal grains (maize, sorghum, rice, teff and wheat). A. cruentus and A. hypochondriacus can contribute minerals such as calcium, iron and zinc, which are very important for human nutrition. The results of the current study indicate that A. cruentus and A. hypochondriacus can provide better nutritional values and mineral content with a minimum value of anti-nutrients that are very important to minimize binds and block the absorption of certain minerals, such as iron, zinc and calcium. Using A. cruentus and A. hypochondriacus alone and with other cereals should be encouraged and recommended for consumption to increase the nutritional composition of diets and decrease food security problem in a study areas. Int. J. Agril. Res. Innov. Tech. 12(2): 36-40, December 2022